Peran Pemerintah dalam Pengembangan Potensi Desa melalui Pendidikan Ekonomi Kreatif - Masruroh, Nikmatul; Suprianik, Suprianik (Civiliza Publishing, Indonesia., 2023)
This research was conducted to obtain data related to the development of the village's creative economy. Then the data is used as a basis for the development of a creative economy so that local village products can be competitive in regional, national, and international markets. Besides being able to compete, these products are also able to survive during the global market and during industry 4.0 competition. The research method used is a qualitative approach, a type of phenomenology. Data collection techniques with observation, interviews, and documentation. Data were analyzed by phenomenological analysis with the stages given by Miles and Huberman, namely data condensation, data presentation and conclusions. Data validity uses source triangulation. The results of this study state that there has been no government involvement in the development of the creative economy in Rowotengah village.